2023
DOI: 10.1108/joepp-10-2022-0304
|View full text |Cite
|
Sign up to set email alerts
|

Using approach-inhibition theory of power to explain how participative decision-making enhances innovative work behavior of high power distance-oriented employees

Abstract: PurposeThis research study investigated the relationship between participative decision-making and innovative work behavior by considering the moderating role of power distance orientation of individuals. Grounded in the approach-inhibition theory of power, the authors proposed that participative decision-making could mitigate perceived power gap and motivate individuals with high power distance orientation to engage more in innovative work behavior.Design/methodology/approachSurvey data were collected from 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…A large body of research suggested that empowering leadership can be positive for employees and organizations, as its behaviors facilitate employees’ intrinsic motivation and the resulting beneficial outcomes such as work engagement, job satisfaction, creativity, extra-role behaviors and work performance [ 10 , 11 , 12 ]. Empowering leadership may create supportive and trusting environments in which leaders show respect for their subordinates [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large body of research suggested that empowering leadership can be positive for employees and organizations, as its behaviors facilitate employees’ intrinsic motivation and the resulting beneficial outcomes such as work engagement, job satisfaction, creativity, extra-role behaviors and work performance [ 10 , 11 , 12 ]. Empowering leadership may create supportive and trusting environments in which leaders show respect for their subordinates [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Autonomy is defined as the ability to move independently to explore opportunities, incorporate business ideas and carry them through to execution (Charoensukmongkol and Pandey, 2023;Lumpkin et al, 2009). Innovativeness is a term used to describe a firm's receptivity to innovative ideas, and thus, depicts the entire organizational culture that encourages novel ideas to be generated, developed or adopted and implements them effectively (Farzana and Charoensukmongkol, 2023;Tuominen et al, 2004). Risk-taking is considered the extent to which management is prepared to allocate substantial resources to explore possibilities in the mid of uncertainty (Lumpkin and Dess, 1996;Miller, 1983;Ratanavanich and Charoensukmongkol, 2024).…”
Section: 23mentioning
confidence: 99%
“…, 2009). Innovativeness is a term used to describe a firm’s receptivity to innovative ideas, and thus, depicts the entire organizational culture that encourages novel ideas to be generated, developed or adopted and implements them effectively (Farzana and Charoensukmongkol, 2023; Tuominen et al. , 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The practice of involving employees in decision-making processes has gained significant traction across various types of organizations, particularly in educational settings, where it is considered a key component of empowering teachers [11,13]. Such participatory decision-making contributes positively to organizational well-being by fostering a sense of ownership and commitment among employees.…”
Section: Introductionmentioning
confidence: 99%